Phytotoxicity of Tagetes erecta L. and Tagetes patula L. on plant germination and growth - Santos, Pamela Cristina dos [UNESP]; Santos, Valter Henrique Marinho dos [UNESP]; Mecina, Gustavo Franciscatti [UNESP]; Andrade, Aníbal Reinaldo de [UNESP]; Figueiredo, Patrícia Aparecida [UNESP]; Oliveira, Vanessa Marques de [UNESP]; Silva, Luciana Pereira; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2015)
This study evaluated the phytotoxic potential and antioxidant activity of Tagetes patula and Tagetes erecta, and total phenols and flavonoids of the extracts were quantified. Laboratory bioassays for both pre- and post-emergence were performed in Lactuca sativa L. seeds and in the Allium cepa seeds test. The antioxidant activity was evaluated by DPPH radical scavenging and reducing power of iron, besides total phenols and flavonoids quantification in the extracts. Thus, was observed a reduction in the mitotic index when in compared with the negative control. Was observed also a reduction the germination and development of tested seedlings and was verified a considerable antioxidant potential and presence of flavonoids and phenolic compounds in the extracts. According to these results, it is possible to conclude that T. erecta and T. patula have phytotoxic compounds that may enhance and expand their use in the management of organic agriculture, mainly in vegetables.
Keywords: Germination; Natural defensives; Herbicides; Organic agriculture